Prevalence and Phenotypic Detection of Carbapenem-Resistant Enterobacter Species from the Clinical Specimens of a Tertiary Care Hospital in Bangladesh - Nazmun Nahar Munny; S M Shamsuzzaman; Tamzeed Hossain; Sumaiya Khatun; Fatima Tuj Johora (Update Dental College, 2023)
Background: Carbapenem-resistant Enterobacter (CRE) is an emerging threat spread rapidly around the world in the past few years, posing substantial hazards to human health. Objective: The study was conducted to evaluate the prevalence of carbapenem resistance and to detect carbapenemase producers phenotypically from patients of a major tertiary care hospital, in Bangladesh. Methods: Prospective cross-sectional study was conducted from July 2018 to June 2019, at the Dhaka Medical College hospital. Patients admitted to different wards, and intensive care units, visited the outpatient department, and samples received in the microbiology department were included in this study. A total of 350 clinical samples were collected, inoculated, and incubated in accordance to the standard protocol. Identification was done using the standard biochemical method. Antimicrobial susceptibility testing of commonly used antibiotics including imipenem was done using Kirby Bauer disk diffusion method. All the clinical isolates of Enterobacter were screened for carbapenem resistance as per CLSI guidelines. Such strains were then subjected to phenotypic confirmation of carbapenemase production by the Modified Hodge test. All isolates that gave a positive screening test were further evaluated for Metallo-β lactamase (MBL) production. MBL was further detected by Combined Disc Test (CD) using a combination of Imipenem and Imipenem-EDTA and double disc synergy (DDS) test. Result: A total of 350 clinical specimens were analyzed, of which 224 (65.14%) isolates yielded growth. Among them, 28 (12.28%) Enterobacter were isolated of which 12 (42.86%) were found to be Imipenem resistant (14.25%) and were labeled 'Carbapenem-resistant Enterobacter" or CRE. Minimum inhibitory concentration (MIC) was determined among the carbapenem-resistant clinical isolates. Modified Hodge test (MHT) performed on the 12 carbapenem-resistant isolates showed 9 (75%) isolates to be carbapenemase enzyme producers. Nine out of twelve carbapenem-resistant isolates are Metallo-beta-lactamase producers detected by combined disc test (CDT) and eight (66.67%) MBL producers detected by DDS test. Conclusion: The finding from this study revealed a high prevalence of carbapenem resistance among isolated Enterobacter species in hospital settings as well as community levels. As there are limited treatment regimens, therefore, the timely and accurate detection of carbapenem-resistant Enterobacter species is essential for the clinical treatment and prevention of infections. Simple phenotypic methods like MHT can be used for the rapid detection of carbapenemases, and these are expected to be used routinely in clinical microbiology laboratories. Update Dent. Coll. j: 2023; 13(1): 17-22